2021
DOI: 10.1093/femsec/fiab082
|View full text |Cite
|
Sign up to set email alerts
|

In situmicrocosms deployed at the coast of British Columbia (Canada) to study dilbit weathering and associated microbial communities under marine conditions

Abstract: Douglas Channel and the adjacent Hecate Strait (British Columbia, Canada) are part of a proposed route to ship diluted bitumen (dilbit). This study presents how two types of dilbit naturally degrade in this environment by using an in situ microcosm design based on dilbit-coated beads. We show that dilbit-associated n-alkanes were microbially biodegraded with estimated half-lives of 57–69 days. n-Alkanes appeared to be primarily degraded using the aerobic alkB, ladA and CYP153 pathways. The loss of dilbit polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This genome also had six copies of alkB/M and was isolated from a PAH-contaminated site [ 44 ]. The high HC degradation potential of other members of this genus has also been reported in the marine ecosystem [ 45 , 46 ]. Rugosibacter aromaticivorans (containing 5, 2 and 2 copies of xylX, ndoB, and tmoA genes, respectively), Pseudoxanthomonas _A spadix _B (with 4, 2 and 2 copies of xylX, todC1 and bphA1 genes, respectively), Thauera sp002354895 (4), Pigmentiphaga sp002188635 (4) are other examples of genomes that have multiple copies of the xylX gene.…”
Section: Resultsmentioning
confidence: 79%
“…This genome also had six copies of alkB/M and was isolated from a PAH-contaminated site [ 44 ]. The high HC degradation potential of other members of this genus has also been reported in the marine ecosystem [ 45 , 46 ]. Rugosibacter aromaticivorans (containing 5, 2 and 2 copies of xylX, ndoB, and tmoA genes, respectively), Pseudoxanthomonas _A spadix _B (with 4, 2 and 2 copies of xylX, todC1 and bphA1 genes, respectively), Thauera sp002354895 (4), Pigmentiphaga sp002188635 (4) are other examples of genomes that have multiple copies of the xylX gene.…”
Section: Resultsmentioning
confidence: 79%
“…This genome also had six copies of alkB/M and was isolated from a PAH-contaminated site [28]. The high HC degradation potential of other members of this genus has also been reported in the marine ecosystem [29] S7 and Supplementary Figure S7). On the other hand, Glutamicibacter mysorens (4), Enteractinococcus helveticum (4), and many other genomes from the Castellaniella, Kocuria, and Halomonas genera, had several pheA copies in their individual genomes.…”
Section: Resultsmentioning
confidence: 57%
“…This genome also had six copies of alkB/M and was isolated from a PAH-contaminated site [28]. The high HC degradation potential of other members of this genus has also been reported in the marine ecosystem [29][30]. Rugosibacter aromaticivorans (containing 5, 2 and 2 copies of xylX, ndoB, and tmoA genes, respectively), Pseudoxanthomonas A spadix B (with 4, 2 and 2 copies of xylX, todC1 and bphA1 genes, respectively), Thauera sp002354895 (4), Pigmentiphaga sp002188635 (4) are other examples of genomes that have multiple copies of the xylX gene.…”
Section: Resultsmentioning
confidence: 99%
“…Also, we cannot exclude the presence of microbes with unknown properties that could be involved in complex degradation mechanisms. Microcosm‐associated microbial communities responding to diluted petroleum products contained metagenome‐assembled genomes representing currently unknown lineages (Schreiber et al, 2021) with potentially novel functions and PAH‐degrading features. Furthermore, Louvado et al (2015) showed that the genomes of PAH‐degrading bacterial isolates from deep‐sea sediments carry potential novel orthologs with low sequence similarity to known genes involved in the initial activation step of xenobiotic degradation pathways.…”
Section: Discussionmentioning
confidence: 99%